2017
DOI: 10.1016/j.ctro.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

P4HA1: A single-gene surrogate of hypoxia signatures in oral squamous cell carcinoma patients

Abstract: Background and purposeHypoxia gene expression signatures are of high prognostic value for head and neck cancer patients. Recently, the prognostic information of a multiple-gene hypoxia signature was found to be provided by the mRNA level of P4HA1 alone (Tawk et al., 2016). Therefore, we studied the prognostic value of P4HA1 in an independent cohort of oral squamous cell carcinoma (OSCC) patients.Material and methodsFrozen tumor samples of 118 adult OSCC patients were analysed for P4HA1 mRNA level by quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 35 publications
(47 reference statements)
2
20
0
Order By: Relevance
“…Interestingly, one research suggested that those three hypoxia signatures might be replaced by P4HA1 [28] and another study also confirmed that P4HA1 was a significantly prognostic factor for oral squamous cell carcinoma patients [29]. We also got a similar result in NPC patients.…”
Section: Discussionsupporting
confidence: 72%
“…Interestingly, one research suggested that those three hypoxia signatures might be replaced by P4HA1 [28] and another study also confirmed that P4HA1 was a significantly prognostic factor for oral squamous cell carcinoma patients [29]. We also got a similar result in NPC patients.…”
Section: Discussionsupporting
confidence: 72%
“…Of note, the authors found a P4HA1-HIF1α positive feedback loop, which regulates the glycolytic and oncogenic activities of PDAC, their stemness and chemoresistance (50). Additionally, high P4HA1 expression is a poor prognostic factor for head and neck squamous cell carcinoma (51), oral squamous cell carcinoma (52), and prostate cancer (53). In ovarian cancer P4HA1 promotes migration, invasion, EMT and metastasis formation (54).…”
Section: Collagen-prolyl Hydroxylation In Cancer Progressionmentioning
confidence: 99%
“…Previously, the increased P4HA1 expression correlates with poor prognosis has been demonstrated in several cancers, including breast cancer, oral squamous cell carcinoma, melanoma, and prostate cancer [55][56][57][58] . However, we know little about how P4HA1 promotes tumor progression in the past.…”
Section: Discussionmentioning
confidence: 96%